Effectiveness of An Audience Response System on Orthodontic Knowledge Retention of Undergraduate Dental Students – a Randomised Control Trial. (December 2015) - Robson, Nicholas; Popat, Hashmat; Richmond, Stephen; Farnell, Damian J. J.
Objective: To determine the effect of an audience response system (ARS) on knowledge retention of dental students and to gauge student perceptions of using the ARS. Design: Randomised control study. Setting: School of Dentistry, Cardiff University. Participants: Seventy four second-year dental students were stratified by gender and randomised anonymously to one of two groups. Methods: One group received a lecture on orthodontic terminology and diagnosis in a traditional didactic format and the other received the same lecture integrated with ARS slides. Students completed an assessment of multiple-choice questions (MCQs) scored out of 20, before and immediately after the lecture. Students were also asked to complete a self-reported questionnaire on their perceptions of ARS. Results: Both groups had statistically significant increases in MCQ scores post-lecture (ARS mean increase 3.6 SD2.0, 95% CI 2.2–3.5 and Didactic mean increase 2.9 SD2.3, 95% CI 2.8–4.3). A mixed-design analysis of variance showed that ARS led to an improved MCQ score (by 0.8 or 25%) compared to the didactic group, although this effect was not significant ( P = 0.15). The effect of gender at baseline ( P = 0.49), post-lecture ( P = 0.73) and increase in MCQ score split by group ( P = 0.46) was also not significant. Students reported that the ARS was easy to use, helped them engage with the lecture and encouraged them to work harder. Conclusion: The ARS did not lead to a significant increase in short-term orthodontic knowledge recall of students compared with didactic teaching. However, the use of ARS within orthodontic teaching could make lectures more interactive and engaging.